The impact of Xiaohongshu as the primary information hub: a case study among utar undergraduates - Eu, Jin Hau (2025)
This study investigates the increasing popularity of Xiaohongshu (RedNote) as the primary information hub among Malaysian university students, indicating a behavioural shift away from traditional search engines like Google. Xiaohongshu, once a Chinese e-commerce and lifestyle platform, has transformed into a dynamic space for peer-generated content that combines community interaction, visual storytelling, and authenticity. According to Uses and Gratifications Theory (UGT), this study investigates how well the platform meets students' cognitive, affective, personal, social, and escapist needs. A qualitative case study approach was used, with a focus on a small group of five female undergraduate students from Universiti Tunku Abdul Rahman (UTAR) who actively use Xiaohongshu. The study uses semi-structured interviews and thematic analysis to explore how students use the platform for personal development, travel planning, beauty tips, lifestyle advice, and food recommendations. Interviewees rate Xiaohongshu as more relatable and engaging than Google, noting its visual content, user experiences, and community-driven feedback. Trust is established not through formal expertise, but rather through peer comments, relatable influencers, and perceived authenticity. While students appreciate the platform's speed, convenience, and emotional appeal, they remain concerned about the lack of professional verification, hidden advertising, and algorithmic repetition. Some users have taken on more critical behaviours, such as fact-checking and assessing creator credibility. This study highlights a broader shift in digital literacy, in which students actively engage with emotionally resonant and socially validated content rather than passively consuming it. The findings have practical implications for educators, marketers, and platform developers who want to tailor communication strategies to the preferences of young audiences. Understanding Xiaohongshu's influence is critical for navigating today's rapidly changing information landscape, in which social validation increasingly shapes trust, identity, and decision-making.